The Effect of Wet and Dry Heating Process and Wheat Flour Particle Sizes on Dough Rheology and Staling of Bread - Mohammad Fazli Rad; Jafar Milani; Sepide Haghighat (مجله پژوهش‌های علوم و صنایع غذایی ایران)
IntroductionWheat plays a major role in global nutrition but it cannot be used without processing. The nutritional importance of wheat flour is due to the presence of gluten proteins that create viscoelastic properties. Gluten as a protein inhibits the staleness of bread. Physical modification of flour is a safe method without using any kind of chemicals. Physical modification of flour includes heat treatment and particle size classification. Particle size distribution is the most widely used technique for classifying solid particles, which is effective in improving rheological properties by affecting the physicochemical properties of flour during hydration, such as water absorption, solvent retention, sedimentation, and adhesion properties. Heat treatments, depending on the intensity of temperature and process time, by modifying starch granules, denaturing proteins, and deactivating enzymes, reducing microbial load, and even modifying flavor and aroma are suggested as a suitable way to improve the quality of bread, especially for weak flour. Considering that the interaction of particle size with wet and dry heating of wheat flour on the rheological properties of dough and staleness of bread has not been studied so far. In this research, by dividing wheat flour with different particle sizes and using wet and dry heat treatments for modification the functional characteristics of wheat flour and the improvement of the rheological characteristics of dough and staleness of bread were investigated.Materials and MethodsThe content of moisture, pH, ash, protein, and Zeleny number of wheat flour was measured using the AACC standard method (2000), and wet and dry gluten with the standard number (9639-1, 3) was measured. To classify the size of the particles, wheat flour was divided by a shaker sieve with different sizes of 180, 150, and 125 microns, then under the influence of dry heat treatment for 10 minutes at 100 degrees Celsius and moist heat treatment with 16% humidity for 5 minutes at a temperature of 96 degrees Celsius was placed. Materials for bread formulation for 100 g of wheat flour included 58 ml of water, 2.5 g of sugar, 1 g of salt, 1 g of vegetable oil, and 2 g of yeast. The rheological parameters of the dough were measured by an alveography device. To check the staleness of bread during the storage period, moisture tests of core and shell, blue activity of core to shell, analysis of bread texture, and DSC were performed. Finally, the factorial test was used to investigate the effects of particle size and heat treatment on wheat flour, and Duncan's multiple range test was used to compare the means at the 5% probability level. Results and DiscussionThe results showed that the effect of particle size and dry heat treatment on dough rheology and water activity of bread core and crust was significant, while moist heat treatment had significantly more bread core moisture (p<0.05). According to the results, dry heat treatment did not affect the texture of bread (p>0.05), while the use of flour obtained from moist heat treatment with a particle size of 180 microns led to the improvement of bread texture by reducing the hardness and chewability (p<0.05). The results of thermal analysis showed that the moist heat treatment sample with a particle size of 180 microns had the lowest enthalpy and was the best sample (p<0.05).ConclusionIn general, the use of flour with a particle size of 180 microns and moist heat treatment to improve the rheological and staling properties of bread were the best examples.